The Deterioration of Agronomical Traits of the Continuous Cropping of Stevia Is Associated With the Dynamics of Soil Bacterial Community - Xu, Xinjuan; Luo, Qingyun; Wei, Qichao; Jiang, Shangtao; Dong, Caixia; Faruque, Mohammad Omar; Huang, Zhongwen; Xu, Zhenghua; Yin, Changxi; Zhu, Zaibiao; Hu, Xuebo (Frontiers in Microbiology, 2022)
Stevia rebaudiana Bertoni is grown world-widely as an important, natural sweetener resource plant. The yield of steviol glycosides (SVglys) is greatly influenced by continuous cropping. In this study, we collected the roots, rhizosphere soils and bulk soils from 2 years of continuous cropping (Y2) and 8 years of continuous cropping (Y8). A high-throughput sequencing technology based on Illumina Hiseq 2500 platform was used to study the structure and diversity of bacterial communities in the roots and soils of stevia with different years of continuous cropping. The results demonstrated that although the content of a group of SVglys were significantly increased in stevia of longer term of continuous cropping, it inhibited the growth of plants and lowered the leaf dry weight; as a result, the total amount of SVglys was significantly decreased. Meanwhile, continuous cropping changed the physicochemical properties and the bacterial composition communities of soil. The different sampling sources of root, rhizosphere soil and bulk soil had no impact on the richness of bacterial communities, while it exhibited obvious effects on the diversity of bacterial communities. Continuous cropping had a stronger effect on the bacteria community composition in rhizosphere soil than in root and bulk soil. Based on Linear discriminant analysis Effect Size (LEfSe), in the rhizosphere soil of Y8, the relative abundance of some beneficial bacterial genera of Sphingomonas, Devosia, Streptomyces and Flavobacterium decreased significantly, while the relative abundance of Polycyclovorans, Haliangium and Nitrospira greatly increased. Moreover, the soil pH and nutrient content, especially the soil organic matter, were correlated with the relative abundance of predominant bacteria at the genus level. This study provides a theoretical basis for uncovering the mechanism of obstacles in continuous stevia cropping and provides a guidance for sustainable development of stevia.